Foreign direct investment and Inclusive green growth in Africa: Energy efficiency contingencies and thresholds - Isaac Kwesi Ofori; Emmanuel Y. Gbolonyo; Nathanael Ojong (African Governance and Development Institute (AGDI), 2022)
Despite the growing number of empirical studies on foreign direct investment (FDI) and energy efficiency (EE) as they relate to green growth, there remains an empirical research gap with respect to whether EE can engender positive synergy with FDI to foster inclusive green growth (IGG) in Africa. Also, little has been done to show the IGG gains from improving EE in both the short and long terms. Thus, this paper aims to investigate whether there exists a relevant synergy between EE and FDI in fostering IGG in Africa by using macrodata for 23 countries from 2000 to 2020. According to our findings, which are based on dynamic GMM estimator, FDI hampers IGG in Africa, while EE fosters IGG. Notably, in the presence of EE, the environmental-quality-deterioration effect of FDI is reduced. Additional evidence by way of threshold analysis indicates that improving EE in Africa generates positive sustainable development gains in both the short and long terms. This study suggests that a country's drive to attract FDI needs to be accompanied by appropriate policy options to promote energy efficiency.
Keywords: F2; F21; O11; O44; O55; Q01; Q43; Q56; 330; Africa; Energy efficiency; FDI; Inclusive Green Growth; Greenhouse Gases; Environmental Sustainability